Knowledge of dental caries and salivary factors related to the disease: influence of the teaching-learning process - Naiara de Paula FERREIRA-NÓBILO; Cínthia Pereira Machado TABCHOURY; Maria da Luz Rosário de SOUSA; Jaime Aparecido CURY (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Knowledge of factors related to caries and the possible consequences in controlling the disease may show the use of education as a relevant tool for achieving success in terms of dental health maintenance. Therefore, the aim of the present study was to investigate the relationship between acquired knowledge and salivary factors related to dental caries for freshmen students (n = 44) and trainees (n = 32) of the Piracicaba Dental School. Knowledge about dental caries was evaluated by a discursive questionnaire analyzed by the content analysis technique. Salivary flow and pH, buffer capacity, salivary sucrase activity, microbiological counts (total microorganisms, mutans, and lactobacilli) and inorganic concentration of calcium, phosphorus, and fluoride in saliva were evaluated and compared between groups using the Mann-Whitney test, with a significance of 5%. Trainees demonstrated knowledge of the disease, whereas freshmen showed unspecific and confusing concepts. Among the factors analyzed, statistically significant differences were observed for pH, buffer capacity, sucrase activity, total microorganisms, and calcium and fluoride concentrations in saliva. Knowledge about the disease increases and improves over time during the undergraduate program (highest among trainees); although the students from the final year of the program consume more sugar than those from the previous one, they try to balance this activity with greater exposure to fluorides.